A Cephalometrıc Study Of The Soft-Tıssue Changes Resultıng From The Orthodontıc Treatment Wıth Extractıons - Adnan Günnar; İsmail Ceylan; Muzaffer Gülyurt (Galenos Yayinevi, 1995)
The material of the present study consists of pre and posttreatment lateral cephalometric head films of 25 subjects, 13 females and 12 males. The measurements introduced by Holdaway, Ricketts, Steiner, and Merrifield were used to determine the soft-tissue changes concerning the orthodontic treatment. A control group composed of the pre and postcontrol lateral cephalometric head films of 10 girls and 10 boys was employed to eliminate the growth changes. Male and female subjects were separately studied, since statistically significant sex differences were found in most of the parameters of treatment and control groups. The measurements obtained from pre and posttreatment films and from pre and postcontrol films were examined by paired t test. As a result, it has been found in female treatment group that the changes of nose prominence, lip protrusion, lower lip to S line, nasal tip to H line, upper lip to S line, superior sulcus depth, and soft-tissue chin thickness were statistically significant at different levels. In the male treatment group, the changes of superior sulcus depth, inferior sulcus to the H line, upper lip to S line, and nasal tip to H line were significant at 0.05 level. In control groups, the changes of basic upper lip thickness and total chin measurement were statistically significant at 0.05 level in males, while the changes of soft tissue facial angle, basic upper lip thickness, upper lip strain measurement, and total chin measurement were significant at different levels in females. In order to eliminate the growth changes, the first measurements were subtracted from the seconds in both treatment and control groups, and the measurement differences of treatment and control groups were analysed by student's t test. As a conclusion, it has been found that pronounced soft-tissue changes were observed in females, while the soft-tissue changes were minimal in males.